Advances in Interdisciplinary Research: Pioneering Innovations and Sustainable Practices Towards Open Science (Routledge Research in Higher Education, 2025)
This book explores methodologies and strategies for enhancing educational practices through interdisciplinary research and open science. Featuring global contributions, it shows how integrating diverse disciplines can drive innovation, improve teaching, and tackle modern educational challenges. The book begins by highlighting the value of interdisciplinary research, technological advancements, and innovative processes for enriching education. It includes theoretical frameworks for frontier research, practical data visualization strategies, and inclusive approaches to diversity in higher education. Readers will find discussions on knowledge transfer for social impact and guidelines for integrating equity, diversity, and inclusion in open education. It also emphasizes academic networking and personal branding, offering insights into fostering collaboration and professional development. This resource highlights both the theoretical and practical benefits of interdisciplinary research and open science. Valuable for researchers, students, and decision‑makers interested in advancing educational research, promoting inclusive practices, and emerging educational technology, this book contributes to the discourse on educational innovation and provides essential tools and concepts for advancing educational research and practice.